Invasion of shoot apical meristems by Chrysanthemum stunt viroid differs among Argyranthemum cultivars - Zhang, Zhibo; Lee, YeonKyeong; Spetz, Carl; Clarke, Jihong Liu; Wang, Qiaochun; Blystad, Dag-Ragnar (Frontiers in Plant Science, 2015)
Chrysanthemum stunt viroid (CSVd) is a damaging pathogen attacking Argyranthemum plants. Our study attempted to reveal distribution patterns of CSVd in shoot apical meristems (SAM) and to explore reasons for differential ability of CSVd to invade SAM of selected Argyranthemum cultivars. Symptom development was also observed on greenhouse-grown Argyranthemum plants. Viroid localization using in situ hybridization revealed that the ability of CSVd to invade SAM differed among cultivars. In diseased ‘Yellow Empire’ and ‘Butterfly’, CSVd was found in all tissues including the uppermost cell layers in the apical dome and the youngest leaf primordia 1 and 2. In diseased ‘Border Dark Red’ and ‘Border Pink’, CSVd was detected in the lower part of the apical dome and elder leaf primordia, leaving the upper part of the apical dome, and leaf primordia 1 and 2 free of viroid. Histological observations and transmission electron microscopy showed similar developmental patterns of vascular tissues and plasmodesmata in the SAMs of ‘Yellow Empire’ and ‘Border Dark Red’, while immunolocalization studies revealed a major difference in the number of callose (β -1, 3-glucan) particles deposited at plasmodesmata in SAM. A lower number of callose particles were found deposited at plasmodesmata of SAM of ‘Yellow Empire’ than ‘Border Dark Red’. This difference is most likely responsible for the differences in ability of CSVd to invade SAM among Argyranthemum cultivars.